Transition metal catalysis-a unique road map in the stereoselective synthesis of 1,3-polyols - Kumar, Pradeep; Tripathi, Divya; Sharma, Brijesh M.; Dwivedi, Namrata (Organic & Biomolecular Chemistry, 2017)
The present review summarizes recent diverse reactions employed in the formation of 1,3-polyols providing an overview of the mechanistic pathway and the enantioselectivity obtained, in terms of the properties of transition metals directly involved in the catalytic transformations and their interaction with various ligands.